Tertiary educators' mental health and likelihood of seeking for counseling help - Ho, Chea Khai; Abdul Kadir, Rusnani (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
This study was aimed to describe more regarding Malaysia tertiary educators and their mental health. This was a descriptive study and there were inferential information being provided in current study. Four selected faculties; mental health scoring was obtained by 12-items General Health Questionnaire. Demography statuses, perceptions, experiences and likelihood of seeking for counseling help, and the mental health among educators in were discussed. There were perceptions found to have significant relationships with GHQ; perceived stress, job satisfaction, and effectiveness of career counseling, and there was significant difference between mental health scores for Hard science and Social science. New findings could be useful to develop plans for increasing mental health among educators in the university.